Великдень – найбільше християнське свято - Кулічко-Павленко, І. С. (ХНУРЕ, 2020)
Easter, also called Pascha (Greek, Latin or Resurrection Sunday, is a festival and holiday commemorating the resurrection of Jesus from the dead, described in the New Testament as having occurred on the third day after his burial following his crucifixion by the Romans at Calvary c. 30 AD It is the culmination of the Passion of Jesus, preceded by Lent (or Great Lent), a 40-day period of fasting, prayer, and penance. Великдень – найбільше християнське свято. Цей день вважається днем Воскресіння Ісуса Христа і має ще одну назву – Пасха. Святкувати Пасху в Україні почали наприкінці першого тисячоліття з приходом християнства.
Keywords: культурне розмаїття; українознавство; традиції; культура